Ethical Context and Ethical Decision Making: Examination of an Alternative Statistical Approach for Identifying Variable Relationships - Valentine, Sean (Journal of business ethics, 2014)
The purpose of this study was to investigate the relationship between organizational ethical context and the individual ethical decision-making process. In addition, a new statistical approach combining cluster and discriminant analyses was developed to overcome violations of regression assumptions, which are commonly not identified and/or ignored in behavioral and psychological research. Using regressions and this new alternative method, the findings indicated that ethical context does indeed influence the various components of ethical reasoning. However, social desirability was the strongest predictor of ethical decision making, which raises new concerns about how this bias can confound business ethics research. Finally, the findings showed that the alternative method provided more useful and interpretive results, indicating that it has the capacity to influence future empirical work in the field of business ethics, particularly when dealing with data that do not satisfy regression assumptions. The implications and limitations of the study are discussed, and several noteworthy suggestions for future research are provided.